Effects of taper on endurance cycling capacity and single muscle fiber properties - Neary, J. P.; Martin, T. P.; Quinney, H. A. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: It was hypothesized that metabolic adaptations in single muscle cells after a taper period are fiber type (I and II) specific and protocol regimen dependent. METHODS: After 7-wk intensive endurance training, 22 male cyclists (VO2max=4.42 +/- 0.40 L.min(-1)) were randomly assigned to one of three 7-d taper groups: the control group (CON, N=7) continued weekly training, the first experimental group (INT) maintained training intensity but reduced duration (N=7), and the second experimental group (DUR) maintained training duration but reduced exercise intensity (N=8). Each cyclist completed a simulated 40-km time trial (40TT) before and after tapering on a set of wind-loaded rollers using their own bicycle. Muscle biopsies were taken immediately before the 40TT both before and after tapering, and analyzed for mATPase, succinate dehydrogenase (SDH), cyctochrome oxidase (CYTOX), alpha-glycerolphosphate dehydrogenase (alpha-GPD), and beta-hydroxyacyl CoA dehydrogenase (beta-HOAD) in Type I and II fibers, separately, using quantitative histochemistry. RESULTS: The results showed significant (P< or =0.05) increases in SDH (Type I) and mATPase, CYTOX, beta-HOAD, and SDH (Type II fibers) in the INT group, and significant increases in CYTOX (Type I) and beta-HOAD (Type I and II fibers) in the DUR group. Regression analysis showed that the change (posttaper minus pretaper) in simulated 40-km endurance time was correlated with the change in CYTOX and SDH activity for all groups combined (r2=0.62-0.72). CONCLUSION: These results demonstrated that the metabolic properties of different fiber types are altered with tapering, that the type of taper protocol used influences their physiological adaptation, and that improvements in simulated 40-km endurance time were related to changes in metabolic properties of the muscle at the single fiber level.